YIELD SUSTAINABILITY UNDER LONG TERM RICE - RICE CROPPING SYSTEM - S. NARENDAR REDDY, M. SURESH, G. JAYASREE, G. PADMAJA, M. MALLAREDDY and (The Journal of Research, PJTSAU, 2019)
A long-term experiment is being conducted with the objective of studying crop productivity and yield sustainability and under continuous rice-rice cropping system under the influence of different nutrient management practices at Regional Agricultural Research station, Polasa, Jagtial, Telangana. This experiment was initiated in kharif 2000-01. Treatments (12) consist of different doses, integrated nutrient management, only FYM application, control and one fallow. The present study was conducted during rabi 2014-15 and kharif 2015-16. The sustainability yield index in both seasons was found to be highest with integrated nutrient management (100 % NPK + 10 t FYM ha-1 ) (0.617 and 0.615 in rabi and kharif respectively) followed by 150 % NPK (0.615 and 0.605). It was least under imbalanced fertilizer application of only N (0.508 and 0.571) followed by control (0.542 and 0.564).